Evaluation of indocyanine green antimicrobial photodynamic therapy in radical species elimination: an in vitro study - Mihail Z. Tanev; Georgi T. Tomov; Kostadin G. Georgiev; Ekaterina D. Georgieva; Kamelia V. Petkova-Parlapanska; Galina D. Nikolova; Yanka D. Karamalakova (Folia Medica)
Introduction: Antimicrobial photodynamic therapy (aPDT) utilizes light-sensitive materials to inactivate pathogens. Indocyanine green (ICG) is an FDA-approved photosensitizer known for its effective photo-thermal and photo-chemical properties. Aim: This study evaluates the efficacy of ICG-based aPDT in eliminating reactive species compared to methylene blue (MtB) using electron paramagnetic resonance (EPR) spectroscopy. Materials and methods: Solid samples of ICG and MtB were prepared at 0.33% concentrations. Solutions were irradiated with lasers at 810 nm and 630 nm, respectively. EPR spectroscopy measured reactive oxygen species (ROS) and reactive nitrogen species (RNS). Spin-trapping agents assessed alkyl radicals, superoxide, and singlet oxygen. Results: ICG demonstrated higher scavenging activity for ROS/RNS compared to MtB. Under PDT, ICG significantly enhanced the reduction of photooxidative stress markers in vitro. Conclusions: ICG combined with aPDT is more effective than MtB in reducing ROS/RNS, indicating its potential for enhanced antimicrobial applications.